(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the impact of board structure on corporate financial performance in Nigeria. It investigates the Diversity of boards of directors in Nigerian firms and analyses whether board structure has an impact on financial performance, as measured by return on equity (ROE) and return on capital employed (ROCE). Based on the extensive literature, four board characteristics (board Diversity, board size, board ownership and CEO duality) have been identified as possibly having an impact on corporate financial performance and these characteristics are set as the independent variables. The Ordinary Least Squares (OLS) regression was used to estimate the relationship between corporate performance measures and the independent variables. Findings from the study show that there is strong positive association between board size and corporate financial performance. Evidence also exists that there is a positive association between outside directors sitting on the board and corporate financial performance. However, a negative association was observed between directors’ stockholding and firm financial performance measures. In addition, the study reveals a negative association between ROE and CEO duality, while a strong positive association was observed between ROCE and CEO duality. The study suggests that large board size should be encouraged and the Diversity of outside directors as members of the board should be sustained and improved upon to enhance corporate financial performance.